Circularly polarized D‐shaped slot antenna for wireless applications. Issue 1 (19th November 2018) - Kunwar, Alaknanda; Gautam, Anil Kumar; Kanaujia, Binod Kr; Rambabu, Karumudi
Abstract: A multiband circularly polarized slot antenna for wireless local area networks (WLAN) and worldwide interoperability for microwave access (WiMAX) applications is designed, studied, and fabricated. Using modified ground plane structure, circular polarized characteristics are realized. An open rectangular loop is introduced on the ground plane to generate orthogonal modes at middle resonance frequency. At higher resonance frequency to improve axial ratio bandwidth, a D‐shaped radiator is used. Thus, the cooperation of modified ground plane, open loop resonator, and D‐shaped radiator improves performance of the antenna at all the required bands. The proposed microstrip antenna generates separate impedance bandwidths to cover frequency bands of WLAN and WiMAX applications. The realized antenna is relatively small in size 40 × 54 mm 2 or 0.26_ × 0.36_ where _ is the free‐space wavelength at the desired first resonant frequency 2.0 GHz and operates over frequency ranges 26% (2.0‐2.6 GHz), 8.9% (3.21‐3.51 GHz), and 50.6% (3.8‐6.38 GHz). In addition, the antenna exhibits 5% (2.32‐2.44 GHz), 5.8% (3.3‐3.5 GHz), and 5.2% (5.61‐5.91 GHz) Circular Polarization bandwidth, making it suitable for WLAN and WiMAX applications.